Effects of fear of falling and activity restriction on normal and dual task walking in community dwelling older adults - KENNY, ROSE; DONOGHUE, ORNA; CRONIN, HILARY; SAVVA, GEORGE; O'REGAN, CLAIRE (My University, 2013)
Fear of falling (FOF) is associated with poor physical and psychosocial health and can have debilitating consequences especially when it leads to activity restriction. This study examined whether normal and dual task gait disruptions were independently associated with FOF and activity restriction or if they were fully explained by impaired health status. Data was obtained from The Irish Longitudinal Study on Ageing (TILDA). Community dwelling adults ?65 years, with a Mini-Mental State Examination score ?18 and who completed a gait assessment (n = 1307) were divided into three groups: no FOF, FOF but no activity restriction (FOF-NAR), FOF with activity restriction (FOF-AR). Physical, psychosocial and cognitive measures were obtained and gait characteristics were assessed using a GAITRite ? mat during normal and dual task (cognitive) walking. After adjusting for sociodemographics, physical, mental and cognitive health, FOF was associated with reduced gait speed and stride length and increased double support phase and step width in normal and dual task conditions; these changes were most pronounced in those who restrict activities as a result of FOF. These gait changes may be associated with an increased fall risk, however some changes especially increased step width may also reflect positive, compensatory adaptations to FOF. The results also highlight the importance of treating underlying health impairments and preventing the transition from FOF to activity restriction
PUBLISHED
PMID: 23200462
Keywords: Ageing; Ageing